Creative expressive activities and Asperger's syndrome : social and emotional skills and positive life goals for adolescents and young adults - Martinovich, Judith, 1955- (Jessica Kingsley, 2006)
Individuals with Asperger's Syndrome (AS) benefit from a positive, affirming support of their individuality. This forward-looking book focuses on building individual strengths and resilience, rather than modifying perceived weaknesses, through individualized therapy within a group context. Integrating psychological and educational theory with a variety of creative therapies, Judith Martinovich combines activities such as art making, drama, music, puppetry, yoga and photography with conventional cognitive-behavioural interventions to support individuals with AS. The different activities complement and reinforce each other and are designed to address specific traits of the autism spectrum to aid skills development. Although created primarily for use with adolescents and young adults, the practical and versatile activities can be adapted for different age and skill levels, objectives and settings. Informed by contemporary research, they meet the objectives of a framework of principles drawn from Positive Psychology and Social and Emotional Learning. Creative Expressive Activities and Asperger's Syndrome is a comprehensive resource for parents as well as teachers, social workers, psychologists and arts therapists who wish to link therapeutic goals with creative activities for people with or without Asperger's Syndrome.